Tendon injuries basic science and clinical medicine - Maffulli, Nicola; Renstrom, Per; Leadbetter, Wayne B. (Springer, 2005)
Provides the knowledge and scientific basis for practitioners to tackle upper and lower limb tendon ailments. With an increasing problem of tendon morbidity in athletes, this book outlines the necessary practical approach when undertaking complex clinical decisions. It provides a comprehensive review of tendon disorders.